Male Macrophages and Fibroblasts from C57/BL6J Mice Are More Susceptible to Inflammatory Stimuli - Barcena, Maria Luisa; Niehues, Maximilian H.; Christiansen, Céline; Estepa, Misael; Haritonow, Natalie; Sadighi, Amir H.; Müller-Werdan, Ursula; Ladilov, Yury; Regitz-Zagrosek, Vera (Frontiers in Immunology, 2021)
Mounting evidence argues for the significant impact of sex in numerous cardiac pathologies, including myocarditis. Macrophage polarization and activation of cardiac fibroblasts play a key role in myocardial inflammation and remodeling. However, the role of sex in these processes is still poorly understood. In this study, we investigated sex-specific alterations in the polarization of murine bone marrow-derived macrophages (BMMs) and the polarization-related changes in fibroblast activation. Cultured male and female murine BMMs were polarized into M1 (LPS) and M2 (IL-4/IL-13) macrophages. Furthermore, male and female cardiac fibroblasts were activated with TNF-α, TGF-β, or conditioned medium from M1 BMM. We found a significant overexpression of M1 markers (c-fos, NFκB, TNF-α, and IL-1β) and M2 markers (MCP-1 and YM1) in male but not female activated macrophages. In addition, the ROS levels were higher in M1 male BMMs, indicating a stronger polarization. Similarly, the pro-fibrotic markers TGF-β and IL-1β were expressed in activated cardiac male fibroblasts at a significantly higher level than in female fibroblasts. In conclusion, the present study provides strong evidence for the male-specific polarization of BMM and activation of cardiac fibroblasts in an inflammatory environment. The data show an increased inflammatory response and tissue remodeling in male subjects.